Acceptability of Self-Sampling for Cervical Cancer Screening Among Women Living With HIV and HIV-Negative Women in Limbé, Cameroon - Pierz, Amanda J.; Ajeh, Rogers; Fuhngwa, Norbert; Nasah, Judith; Dzudie, Anastase; Nkeng, Relindis; Anastos, Kathryn M.; Castle, Philip E.; Adedimeji, Adebola (Frontiers in Reproductive Health, 2021)
Introduction: Like many countries in Sub-Saharan Africa, Cameroon has a high burden of cervical cancer and low availability and uptake of screening. Self-collection has the potential to increase the uptake of cervical cancer screening among Cameroon women. This paper explores patient and community insights surrounding self-collection among women living with HIV and HIV[-] women as well as the barriers and facilitators to obtaining and utilizing self-collected specimens in cervical cancer screening programs. Materials and Methods: We utilized an exploratory qualitative approach to obtain data through focus group discussions and in-depth interviews during data collection that took place from May to August 2018. A two-stage sampling strategy was used to select 80 women who participated in 6 focus group discussions and 8 in-depth interviews. We utilized the socio-ecological framework to guide data analysis. Results: All participants indicated that self-sampling was an acceptable method of specimen collection and should be offered as an option for cervical cancer screening in Cameroon. Whereas most women, regardless of HIV status, preferred the option for self-collection, barriers were identified, such as lack of education about self-collection procedure, being uncomfortable, embarrassed or in pain from the procedure, fear of consequences, perceived competence about ability to self-collect and privacy & confidentiality. We also found that HIV-related stigma was a major concern for HIV[-] women that could prevent them from accessing cervical cancer screening integrated within HIV treatment settings. Conclusions: To promote self-collection for cervical cancer screening, educational interventions with both patients and providers are necessary to increase knowledge of and overall willingness to utilize self-collection. Further research is recommended to examine the role of stigma for HIV[-] women in screening locations associated with HIV treatment.